AS Level Psychology : The study guide - Holt, Nigel; Lewis, Rob. (Bancyfelin : Crown House, 2008)
This textbook, written for the 2008 AQA 'A' Psychology syllabus, covers the whole specification in colour-coded, clear and concise chapters. Each chapter is well illustrated with photos and diagrams and contains key studies and vignettes to engage the student.
Includes index.
Keywords: Psychology -- Examinations -- Study guides; Psychology